Bio-fertilizer application induces soil suppressiveness against Fusarium wilt disease by reshaping the soil microbiome. (November 2017) - Xiong, Wu; Guo, Sai; Jousset, Alexandre; Zhao, Qingyun; Wu, Huasong; Li, Rong; Kowalchuk, George A.; Shen, Qirong
Abstract: Fusarium wilt disease is a growing problem in agriculture systems. Application of bio-fertilizers containing beneficial microbes represents a promising disease control strategy. However, the mechanisms underlying disease suppression remain elusive. Here, in order to assess the importance of direct antagonism and modified soil microbiota on suppression of Fusarium wilt disease, we conducted a pot experiment with chemical, organic and biologically enhanced fertilizers, we tracked the impact of those fertilizer amendments on disease incidence, and measured the pathogen density and changes in soil microbiota. Alterations in bacterial abundance and community structure after bio-fertilizers application were determined to be key factors in constraining the pathogen, Fusarium oxysporum . In particular, bio-fertilizer application increased the abundance of indigenous microbial groups with reported antifungal activity, such as Lysobacter spp., which could play a keystone role in controlling this pathogen. The microbes introduced in the bio-fertilizer treatments ( e.g. Bacillus and Trichoderma spp.) induced suppressiveness via alteration of the soil microbiome rather than direct pathogen inhibition. These results contrast with the commonly held paradigm of disease suppression using beneficial microbes and open up new perspectives for the promotion of soil health. In addition to seeking antagonistic microbes based on their direct inhibitory activity, disease suppression may also be achieved by introducing keystone species that reshape soil microbiome structure and function. Highlights: Bio-fertilizer application induced soil suppression against Fusarium wilt disease. Lysobacter spp. abundance was increased and negatively correlated with F. oxysporum abundance. Alterations in bacterial abundance and community structure play a key role against F. oxysporum. Alterations of soil microbiome rather than direct antagonism induced disease suppressiveness.